13. ANTIBIOTICS IN PEDIATRIC PATIENTS WITH ASTHMA (Vietnam Journal of Community Medicine, 2023)
Objective: To survey the situation of antibiotic use in pediatric patients with asthma at Vinh Long Provincial General Hospital. Subjects and methods: Cross-sectional descriptive study, 104 children diagnosed with asthma, inpatient treatment at Vinh Long Provincial General Hospital.Results: In patients with asthma without superinfection, the majority of patients were prescribed antibiotics alone (92.5%). Meanwhile, in pediatric asthma with superinfection, more combination regimens were indicated (52.5%). In the monotherapy regimen, the most commonly used antibiotic was Ceftazidin. Besides, the combination regimen used was Ceftriazone + Macrolid and Ceftazidin + Macrolid. Among those with no evidence of infection, antibiotic use was associated with a longer hospital stay compared with the group who did not use antibiotics. Conclusion: In patients with asthma without superinfection, the majority of patients were assigned to use antibiotics alone, pediatric patients with superinfected asthma mainly used combination regimens. In the single regimen, the most used antibiotic is Ceftazidin. The combination regimen usually uses Ceftriazone + Macrolid and Ceftazidin + Macrolid.
Keywords: Antibiotics, Pediatric patients, Asthma.